Library lion - Knudsen, Michelle; Hawkes, Kevin (Walker Books London, 2008)
"Library Lion" is a delightful children's book that tells the story of a lion who loves to read. This gentle giant spends his days exploring the library, borrowing books, and sharing his love of reading with others. Through this heartwarming tale, children learn the importance of reading, imagination, and the power of friendship.